Temperature dependency of element incorporation into European eel (Anguilla anguilla) otoliths - Marohn, Lasse; Hilge, Volker; Zumholz, Karsten; Klügel, Andreas; Anders, Heike; Hanel, Reinhold (Analytical and Bioanalytical Chemistry, 2011)
The present study experimentally tested the influence of water temperature on the inclusion of 15 elements into juvenile European eel (Anguilla anguilla) otoliths in freshwater. It should be investigated (1) if temperature effects on otolith Sr/Ca might impair the interpretation of migration studies and (2) if the elemental composition of otoliths can be used to reconstruct experienced temperature histories of eels. Therefore, eels were kept under full experimental conditions at three different water temperatures (14 °C, 19 °C and 24 °C) for 105 days. Thereafter, laser ablation inductively coupled mass spectrometry (LA-ICPMS) was conducted on the outer edge of their otoliths. Our analyses revealed significant temperature effects on otolith Na/Ca, Sr/Ca, Mg/Ca, Mn/Ca, Ba/Ca, Zr/Ca and Y/Ca ratios. Variations of Sr/Ca caused by temperature were far below those used to detect eel movements between waters of different salinities and will therefore not affect the interpretation of migration studies. Elemental fingerprints of Sr/Ca, Mg/Ca, Mn/Ca and Ba/Ca ratios resulted in clearly separated groups according to temperature treatments, indicating that changes in water temperature might lead to characteristic changes in otolith element composition. However, the successful application of elemental fingerprints to reconstruct moderate changes of water temperature seems doubtful because the influence of somatic growth on otolith microchemistry still remains unclear, and temperature-induced variations could be overlaid by changes of water element concentrations during growth periods. Nevertheless, our results contribute to the completion of knowledge about factors influencing element incorporation and help to explain variations in element composition of fish otoliths.